2021
DOI: 10.3390/su13179948
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Profiles in the WISC-V of Children with ADHD and Specific Learning Disorders

Abstract: Attention Deficit Hyperactivity Disorder (ADHD) has a high comorbidity with specific learning disorders (SLD). Children with ADHD and children with SLD show specific cognitive deficits. This study aims to examine similarities and differences between cognitive profiles of children with ADHD + SLD, children with SLD only, and a control group to find out whether specific or shared deficits can be identified for the groups. We compared the WISC-V profiles of 62 children with ADHD and SLD (19 girls, M-age = 10.44; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
0
9
0
2
Order By: Relevance
“…Two papers passing initial screening stages were excluded as they included data overlapping with other sources ( Holdnack et al., 2011 ; Theiling et al., 2013 ). One additional paper was identified through review of reference lists of included papers ( Becker et al., 2021 ), and standardization data were included from the WAIS-IV and WISC-V (however, as Dale et al., 2022 used standardization data in their analysis, the WISC-V had effectively already been counted as a data source). This gave a total of 18 sources of cross-sectional data included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two papers passing initial screening stages were excluded as they included data overlapping with other sources ( Holdnack et al., 2011 ; Theiling et al., 2013 ). One additional paper was identified through review of reference lists of included papers ( Becker et al., 2021 ), and standardization data were included from the WAIS-IV and WISC-V (however, as Dale et al., 2022 used standardization data in their analysis, the WISC-V had effectively already been counted as a data source). This gave a total of 18 sources of cross-sectional data included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Larger samples were associated with lower scores in children diagnosed with ADHD, so the overall scores may slightly overestimate ability in children with ADHD. This is likely due to a methodological artifact rather than publication bias per se, as one of the two samples contributed by Becker and coworkers (2021) was very small and only consisted of children with no evidence of specific learning difficulties, whereas eligibility criteria in other samples were more inclusive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of SLD is controversial in the case of all children with ADHD. Some studies have argued for important differences between children who have ADHD with versus without SLD (Becker et al, 2021;Crisci et al, 2021;Katz et al, 2011;Parke et al, 2020), but a recent study found that this was not the case (Toffalini et al, 2022). Examining the case of twice-exceptional children (identified on the basis of a high GAI) brought more light on the cognitive processes that support academic learning (working memory and processing speed) specifically in the case of intellectual giftedness.…”
Section: Discussionmentioning
confidence: 99%
“…The fourth matter that our study aimed to examine was whether 2e-ADHD children could also have SLD, as it is quite common to find an associated SLD in the ADHD population (see Pham & Riviere, 2015), and whether there could be differences between 2e-ADHD children with and without SLD. In fact, the few studies that distinguished between children who had ADHD with and without SLD generated different findings (probably due to differences in the samples' characteristics), arguing either for differences in their intellectual profiles (Becker, Daseking, & Koerner, 2021;Crisci, Caviola, Cardillo, & Mammarella, 2021;Katz, Brown, Roth, & Beers, 2011;Parke, Thaler, Etcoff, & Allen, 2020) or for surprising similarities (Toffalini et al, 2022). Examining cases of 2e-ADHD, identified on the strength of a high GAI, could shed important light on cognitive processes (WM and PS) related specifically to intellectual giftedness, by showing whether intellectual similarities between children with ADHD and those with SLD are due simply to the co-occurrence of the two disorders.…”
Section: Cognitive Characteristics Of Intellectually Gifted Children ...mentioning
confidence: 99%